Individual responses to an 8-week neuromuscular training intervention in trained pre-pubescent female artistic gymnasts - Moeskops, S.; Read, P. J.; Oliver, J. L.; Lloyd, R. S. (Sports, 2018)
This study examined individual responses in leg stiffness, reactive strength index (RSI), movement proficiency (deep overhead squat and in-line lunge), and trunk muscular endurance (flexor and extensor tests) in young female gymnasts following an 8-week neuromuscular training intervention. Thirty-four pre-peak height velocity (PHV) female gymnasts were divided into either an experimental group (EXP n = 17) or control group (CON n = 17). The EXP replaced their normal gymnastics physical preparation with a neuromuscular training program, while the CON continued with their habitual gymnastics program. Chi square analysis showed that the EXP resulted in significantly more positive responders compared to CON for measures of leg stiffness (41% versus 12% responded positively), extensor muscular endurance, (76% versus 29%), and competency in the deep overhead squat, (76% versus 29%) and in-line lunge (left lead leg) (65% versus 18%). Conversely, the number of positive responders for RSI (53% versus 61%), the flexor endurance test (88% versus 53%), and the right in-line lunge (47% versus 35%) were not significantly different between groups. These findings suggest that most young gymnasts responded positively to neuromuscular training from the perspective of improving movement proficiency and trunk endurance; however, changes in leg stiffness and RSI were more variable and may require higher intensities to realise further adaptations.